Does insider selling affect audit fees? - Hualing Yang; Yunbiao Ma (China Journal of Accounting Studies (CJAS), 2020)
Using a sample of Chinese A-share listed companies from 2006 to 2016, this paper examines the impact of insider selling on audit fees. The results show that auditors of clients with higher insider selling tend to charge higher fees. Mechanism tests show that the presence of insider selling is associated with a higher level of audit risk, which in turn increases audit fees. Further tests show that, the positive relation between insider selling and audit fees is stronger for non-SOEs and BIG4 audited firms; auditors only charge higher audit fees for share selling of large shareholders and directors. These results indicate that auditors can identify the risk of insider selling and charge higher audit fees, and provide new insight into the economic consequence of insider selling and a new determinant of audit fees.
Keywords: 650; Insider selling; audit fees; audit risk; agency risk; operating risk